Review on multilayer security on Cloud Server - *, Preeti; Kumar, Mahesh (IJRDO -Journal of Computer Science Engineering, 2017)
While Cloud services offer flexibility, scalability & economies of scale, there have been commensurate concerns about security.As more data moves from centrally located server storage to Cloud, potential for personal & private data to be compromised would increase.Confidentiality, availability & integrity of data are at risk if appropriate measures are not put in place prior to selecting a Cloudvendor/implementing your own cloud & migrating to Cloud services. Cloud services such as Software as a service, Platform as a service orInfrastructure as a service would each have their own security concerns that need to be addressed. This paper reviews best practices to secureCloud services & data, including conventional security techniques & working within vendors to ensure proper Service Level Agreements